SISTEM OTOMATISASI SKALA MINI ADSORPSI BESI DALAM AIR ASAM TAMBANG - Paradise, Mycelia; Pratama, Yudha Agung (Jurnal Teknologi Mineral dan Batubara, 2024)
Adsorption is one alternative to acid mine drainage (AMD) management, particularly for reducing heavy metal concentrations. Adsorption is still performed manually at this time. In this study, the adsorption procedure is automated and controlled via Arduino rather than being performed manually. The efficacy of using an Arduino in the adsorption of AMD at a pH of 2.6 and an Fe initial concentration of 42.807 mg/L was assessed by modifying the adsorption time parameters. The results showed that the assembled instrument was able to reduce the Fe concentration to meet the quality standards in just 2 minutes. The effectiveness of Fe adsorption reached 96.79% with a final concentration of 1.3724 mg/L. Fe adsorption capacity reached 0.0414 mg/g in the second minute. The Fe adsorption process in this study is chemical adsorption.